Sports Physiology in Adolescent Track-and-Field Athletes: A Narrative Review - Nikolaidis PT; Son'kin VD (Dove Medical Press, 2023)
Pantelis T Nikolaidis,1 Valentine D Son'kin2 1School of Health and Caring Sciences, University of West Attica, Athens, Greece; 2Russian State University of Physical Education, Sport, Youth and Tourism (SCOLIPE), Moscow, RussiaCorrespondence: Pantelis T Nikolaidis, Email pnikolaidis@uniwa.grAbstract: The present study aimed to review the physiological aspects of adolescent track-and-field (TAF) athletes. A search of Scopus on 27/12/2022 using the syntax ABS (track-and-field) AND ABS (children) OR ABS (adolescent) showed 121 documents, and 45 were considered for further analysis. In addition, handsearching was conducted to identify Russian literature missing in Scopus. Differences were shown in performance characteristics among disciplines, especially between throwers and the other athletes. The sex difference in performance (ie, a better performance in boys than in girls) started in early adolescence. A relative age effect was more pronounced in athletes under 13 years old. Despite the wide use of nutritional supplements, an insufficient intake of vitamins has been found. The age of training onset and body weight were identified as risk factors for problems with menarche. The inclusion of track-and-field training programs in physical education was beneficial for health and physical fitness. The need to collaborate closely with parents and coaches was identified, especially, regarding education in topics such as the age of training onset, relative age effect, and doping. In conclusion, the existence of many disciplines with different anthropometric and physiological characteristics highlighted the need for a discipline-specific approach.Keywords: running, jumping, throwing, speed, strength, endurance, age, maturation